Participatory Evaluation in a Prison Education Program: Meaning & Community Building within Inside-Out Think Tanks. Issue 1 (1st January 2020) - Allred, Sarah L.; Boyd, Charles; Cotton, Thomas; Perry, Paul
ABSTRACT: This article presents the processes associated with a participatory evaluation of alumni groups—Think Tanks—affiliated with the Inside-Out Prison Exchange Program. The participatory evaluation members included people incarcerated (Inside members) and an academic scholar (Outside member). Members were affiliated with Inside-Out and part of their respective Think Tanks. The participatory project yields insights related to having team members who are Inside and Outside people. In several ways, the participatory evaluation members experienced challenges to their working model throughout the project. Data come from nine focus groups convened in eight prisons moderated by the Outside member. The findings describe the personal meanings that Think Tank members attributed to being in the group. The analyses revealed that Think Tank participation represents a significant, positive experience to members. The themes identified to highlight the concepts of individual transformation, relationships, civic engagement, and solace. The perceptions of Think Tank experiences convey substantial individual growth as well as community building within and beyond the group into the general prison population and the outside world.